The Canadian Labour Movement, 1902-1960 - Abella, Irving (Canadian Historical Association, 1975)
If, as Sir Wilfrid Laurier said, the twentieth century would be the century of Canada, by the end of the first decade of the new century it was already apparent that it would not be the century of the Canadian working man. The twentieth century ushered in the great Canadian boom.The twentieth century ushered in the great Canadian boom. And boom conditions produced a boom psychology. Nothing could stop Canada. Incredible industrial expansion; two new transcontinental railways pushing across the West; seemingly unstoppable floods of capital and immigrants pouring into the country; these were the hallmark of the decade. Indeed, everyone seemed to be prospering. Everyone, that is, but the Canadian worker. To him the twentieth century ushered in no new changes - or at least, no changes for the better. His conditions of work were still appalling, and his wages–though somewhat higher–could not keep up with spiralling living costs. Indeed, the influx of hundreds of thousands of hungry, penniless immigrants even made it difficult to hold a job. And what jobs? Stuffy, unventilated factories; sixty hours a week; back-breaking work; all for a dollar a day. These were the conditions of work for the men, women and children of Canada. And a dollar a day was considered excellent pay for the thousands of boys and girls, some not yet in their teens, who were forced to find jobs. –Introduction